Investigating Pre-Service Teachers’ Perceptions of Native and Non-Native English Educators and Speakerism - Rahmah Fithriani; Putri Adinda Pratiwi (LPPM Universitas Advent Indonesia, 2026)
English as a lingua franca (EFL) and World Englishes (WEs) challenge traditional English language teaching paradigms that centred around native-speaker norms, often rooted in the ideology of native speakerism, a persuasive ideology in English language teaching, often leading to biases against No-native English Speaker Teachers (NNESTs). This study aims to understand pre-service English speaker teachers' overall attitudes toward NESTs and NNESTs and explore the factors influencing pre-service English teachers’ preferences. 15 pre-service English teachers in their fifth semester participated in this descriptive qualitative method, which was collected from the questionnaires and interviews. The results show positive attitudes towards NESTs and NNESTs, with a slightly negative attitude towards NNESTs in teaching pronunciation due to native speakerism. In terms of pedagogy, NESTs are engaging and varied in approach, while NNESTs are monotonous but provide bilingual support. Culturally, NESTs provide first-hand exposure, but NNESTs highlight global English diversity. Linguistically, students prefer NESTs for genuine pronunciation of authentic language elements such as slang. These findings reveal there is a tendency for native-speakerism with evidence from participants’ responses. Further studies can expand this research by looking into ways to reduce biases and improve teamwork between NESTs and NNESTs.